2014
DOI: 10.1186/preaccept-1476152043138525
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic filariasis control in Tanga Region, Tanzania: status after eight rounds of mass drug administration

Abstract: LF was still widespread in many parts of Tanga Region after MDA 8, in particular in the coastal areas. This calls for intensified control, which should include increased MDA treatment coverage, strengthening of bed net usage, and more male focus in LF health information dissemination. The low LF burdens observed in some inland districts suggest that MDA in these could be stepped down to provide more resources for upscale of control in the coastal areas. Monitoring should continue to guide the programme to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 22 publications
5
26
0
Order By: Relevance
“…The present communication studies and compares both coverage and impact indicator- Mf prevalence simultaneously. We found an overall 68% percent decrease in microfilaria rate from baseline year 2005 to 2015, similar to other studies [17, 23, 24]. (Fig 2 and Table 5) The evidence confirms that after 10 rounds of MDA, the LF transmission is interrupted and microfilaria rate has decreased to less than 1% in all IUs of Gujarat; threshold level recommended by WHO to provisionally stop MDA [17, 23, 24].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present communication studies and compares both coverage and impact indicator- Mf prevalence simultaneously. We found an overall 68% percent decrease in microfilaria rate from baseline year 2005 to 2015, similar to other studies [17, 23, 24]. (Fig 2 and Table 5) The evidence confirms that after 10 rounds of MDA, the LF transmission is interrupted and microfilaria rate has decreased to less than 1% in all IUs of Gujarat; threshold level recommended by WHO to provisionally stop MDA [17, 23, 24].…”
Section: Discussionsupporting
confidence: 89%
“…Further research and verification in form of surveillance is essential to assure national government that national program have achieved their elimination goals [3, 17, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…The findings of the 2015 survey indicate a remarkable reduction in W. bancrofti CFA prevalence in young children after 12 rounds of MDA. Based on other studies that have reported a reduction in CFA as a result of MDA (Simonsen et al, 2011, Simonsen et al, 2014), the findings suggest a decrease in acquisition of new infections by young school children as a result of MDA.…”
Section: Discussionmentioning
confidence: 51%
“…funestus and Cx. quinquefasciatus were the main vectors of lymphatic filariasis [5, 35, 36] while An. gambiae ( s.l.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria is transmitted by anopheline mosquitoes, while lymphatic filariasis is transmitted by both Anopheles and Culex mosquitoes [2, 4, 5] . These vectors breed in various habitats [6, 7].…”
Section: Introductionmentioning
confidence: 99%